2016
DOI: 10.1002/dys.1550
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension and Generation of Metaphoric Language in Children, Adolescents, and Adults with Dyslexia

Abstract: Difficulties with figurative language comprehension were documented in adult dyslexia (DYS). In the present research, we investigated the comprehension and generation of metaphors in 37 children, 35 adolescents, and 34 adults with and without DYS. We also tested the contribution of executive function to metaphor processing. A multiple-choice questionnaire with conventional and novel metaphors was used to assess comprehension; a concept-explanation task was used to test conventional and novel metaphor generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 62 publications
2
35
1
1
Order By: Relevance
“…However, a number of more recent studies have revealed conflicting findings. In one set of studies, an opposite effect was found such that individuals with dyslexia were less creative than their peers without dyslexia (e.g., Kasirer & Mashal, 2017). This was explained by the facilitation hypothesis , which suggested that fluency in written language facilitates creativity through broadening the range of experiences that one has (Lee & Kim, 2011; Ritchie, Luciano, Hansell, Wright, & Bates, 2013; Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of more recent studies have revealed conflicting findings. In one set of studies, an opposite effect was found such that individuals with dyslexia were less creative than their peers without dyslexia (e.g., Kasirer & Mashal, 2017). This was explained by the facilitation hypothesis , which suggested that fluency in written language facilitates creativity through broadening the range of experiences that one has (Lee & Kim, 2011; Ritchie, Luciano, Hansell, Wright, & Bates, 2013; Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…That is, depending on different sub-types of SLD, inputting information into the central neural system, retrieving information from the brain, and outputting the formulated information may be negatively affected. However, the difficulties demonstrated by children with SLD may result from fundamental deficits in cognitive abilities, such as auditory perception [12][13][14], visual perception [15][16][17], temporal processing [18,19], abstraction [20], memory [21][22][23], or motor functioning [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In studies on adults with SLD, participants especially reported fear of inability, lack of self-confidence, and challenges in affiliation [9]. Kasirer and Mashal (2016) emphasized that children with SLD have challenges in understanding metaphors [10]; semantic challenges in individuals with SLD are considered to affect this ability [11]. Moreover, some studies have reported deficiencies in executive functions (inhibition, set shifting, working memory, etc.)…”
Section: Introductionmentioning
confidence: 99%